2015
DOI: 10.1063/1.4937909
|View full text |Cite
|
Sign up to set email alerts
|

High dislocation density of tin induced by electric current

Abstract: A dislocation density of as high as 1017 /m2 in a tin strip, as revealed by high resolution transmission electron microscope, was induced by current stressing at 6.5 x 103 A/ cm2. The dislocations exist in terms of dislocation line, dislocation loop, and dislocation aggregates. Electron Backscattered Diffraction images reflect that the high dislocation density induced the formation of low deflection angle subgrains, high deflection angle Widmanstätten grains, and recrystallization. The recrystallization gave r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Recently, the authors [24] have theoretically shown that the ionic conductivity could be increased by 6 or 7 orders of magnitude without dendrite formation by introducing parallel straight dislocations into single-crystal solid electrolytes with the dislocation density higher than about 10 17 m −2 . The dislocation density higher than 10 17 m − 2 has not yet been experimentally reported for ceramics except for one case although such the high dislocation densities have been experimentally reported for metals, metalloids, and biomaterials several times [10,[20][21][22][23][28][29][30][31][32]. In order to achieve the extremely high ionic conductivity by the introduction of dislocations without dendrite formation, knowledge on the upper limit of dislocation density that could be introduced in ceramics is desirable.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, the authors [24] have theoretically shown that the ionic conductivity could be increased by 6 or 7 orders of magnitude without dendrite formation by introducing parallel straight dislocations into single-crystal solid electrolytes with the dislocation density higher than about 10 17 m −2 . The dislocation density higher than 10 17 m − 2 has not yet been experimentally reported for ceramics except for one case although such the high dislocation densities have been experimentally reported for metals, metalloids, and biomaterials several times [10,[20][21][22][23][28][29][30][31][32]. In order to achieve the extremely high ionic conductivity by the introduction of dislocations without dendrite formation, knowledge on the upper limit of dislocation density that could be introduced in ceramics is desirable.…”
Section: Introductionmentioning
confidence: 96%
“…It should be noted, however, that dislocation density as high as 10 18 m −2 was experimentally reported near the surface of single-crystal alumina by high-temperature laser shock peening in 2021 by Wang et al [35]. For metals, metalloids, and biomaterials, dislocation density as high as 10 17 m −2 or more has been experimentally reported several times [29][30][31][32]. In metals and metalloids, shock compression [30,31], electric-current stressing [29], and ultrasonic irradiation [36][37][38] have been used to induce the high dislocation density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also other methods such as grinding with sandpaper [48], crystal growth via oriented attachment mechanism [49], cyclic loading of a stainless steel indenter [50], joining of misaligned single crystal surfaces to form a bicrystal interface [3], and growth of thin films with moderate lattice mismatch to the underlying substrate [3].The density of dislocations introduced in ceramics ranges from about 10 12 to 10 16 m −2 while the initial value is about 10 9 to 10 10 m −2 [42,45,46,[50][51][52]. For metals, metalloids, and biomaterials, dislocation density as high as 10 17 m −2 or more has been experimentally reported [53][54][55][56]. In metals and metalloids, shock compression [54,55], electric-current stressing [53], and ultrasonic irradiation [57][58][59] have been used to induce the high dislocation density.…”
Section: Introductionmentioning
confidence: 99%
“…For metals, metalloids, and biomaterials, dislocation density as high as 10 17 m −2 or more has been experimentally reported [53][54][55][56]. In metals and metalloids, shock compression [54,55], electric-current stressing [53], and ultrasonic irradiation [57][58][59] have been used to induce the high dislocation density.…”
Section: Introductionmentioning
confidence: 99%